Togo : Enhanced Initiative for Heavily Indebted Poor Countries- Decision Point Document. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper presents a decision point document for Togo's Enhanced Initiative for Heavily Indebted Poor Countries. Economic performance has been improving although the country has been strongly affected by the recent surge in food and fuel prices as well as heavy flooding during the summer. As a consequence of the extended political crisis, interruption in foreign aid and the economic decline, Togo's social indicators remain among the lowest in the world. Expenditures on health, education, and public investment are far below regional averages.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet